Pengaruh Green Product Dan Green Promotion Terhadap Keputusan Pembelian Produk Tupperware (Studi Kasus Di Kisaran) - Novita, Citani Sriratu; Alfifto, Alfifto (Universitas Medan Area, 2024)
This research aims to determine the influence of Green products and Green promotion on Tupperware Product Purchase Decisions among Tupperware Consumers in Kisaran Baru Village. This type of research uses descriptive quantitative. The population used was Tupperware consumers in Kisaran Baru Village and in this research author uses non-probability sampling. The sample was taken using a purposive sampling method of 98 people. The author uses data collection techniques by observation and distributing questionnaires. Several data analysis methods were used in this research, namely data instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. From the results of the tests carried out in this research, it can be concluded that there is a positive and significant influence between the variables Green product (X1) and Green promotion (X2) partially or simultaneously on the decision to purchase Tupperware products among Tupperware consumers in Kisaran Baru Village